Death by Prison: The Emergence of Life Without Parole and Perpetual Confinement - Seeds, Christopher (University of California Press, 2022)
In recent decades, life imprisonment without the possibility of parole (LWOP) has developed into a distinctive penal form in the United States, one firmly entrenched in US policy-making, judicial and prosecutorial decision-making, correctional practice, and public discourse. LWOP is now a routine practice, but how it came to be so remains in question. Fifty years ago, imprisonment of a person until death was an extraordinary punishment; today, it accounts for the sentences of an increasing number of prisoners in the United States. What explains the shifts in penal practice and social imagination by which we have become accustomed to imprisoning people until death without any reevaluation or expectation of release? Combining a wide historical lens with detailed state- and institutional-level research, Death by Prison offers a provocative new foundation for questioning this deeply problematic practice that has escaped close scrutiny for too long.